Keanekaragaman Serangga di Kebun Teh PTPN VIII di Goalpara Kabupaten Sukabumi - Putriyani, Rida; Saylendra, Andree; Putri, Widia E; Sulistyorini, Endang (JURNAL BUDIDAYA PERTANIAN, 2024)
Insects have an important role in agriculture as pollinators, predators and decomposers, but can also be pests that damage plants and reduce production yields. If farmers can identify pests quickly and precisely based on their symptoms, negative impacts can be minimized. This research aimed to identify insect diversity in the PTPN VIII tea garden in Goalpara, Cisarua Village, Sukaraja District, Sukabumi Regency, West Java, and was conducted from November to December 2023. The method used was descriptive with an exploratory approach. Data was collected through direct observation using yellow traps and pitfall traps at three locations at different heights. As a result, 12 orders and 29 families of insects were found, belonging to Hymenoptera, Entomobryomorpha, Diptera, Araneae, Dermaptera, Orthoptera, Coleoptera, Blattaria, Hemiptera, Lepidoptera, Psocoptera, and Blattodea. The diversity indices at locations I, II, and III were 2.48; 2.23; and 2.17, respectively; whereas the dominance indices were 0.11; 0.16; and 0.13, respectively. In conclusion, insect diversity in the Goalpara PTPN VIII tea garden was classified as moderate, with a low level of dominance, indicating a balanced and stable ecosystem. This research is useful for providing information about the diversity and abundance of insects on the PTPN VIII Goalpara Tea Plantation as well as providing knowledge to farmers about the role of insects on the plantation, including insects that have the potential to act as pests, predators, parasitoids and pollinators.